β-lactolin, a Monoamine Oxidase B Inhibitory Lactopeptide, Suppresses Reactive Oxygen Species Production in Lipopolysaccharide-Stimulated Astrocytes - Shiori Akiyama; Tatsuhiro Ayabe; Chika Takahashi; Rena Ohya; Yasuhisa Ano (Applied Sciences, 2021)
Astrocytes are known to regulate normal brain function. Monoamine oxidase B (MAO-B), an enzyme highly expressed in astrocytes, metabolizes dopamine (DA) and induces reactive oxygen species (ROS) production. We have previously reported that β-lactolin, a whey-derived glycine–threonine–tryptophan–tyrosine tetrapeptide, improves memory impairment in mice by regulating the dopaminergic system; however, the effects of β-lactolin on astrocytes remain unclear. Herein, we investigated the effects of β-lactolin on cultured murine astrocytes. First, we measured intracellular ROS production in lipopolysaccharide-stimulated reactive astrocytes treated with or without β-lactolin, and then determined the role of β-lactolin in DA metabolism in astrocytes by measuring MAO-B enzyme activity and the levels of DA, and its metabolites, in DA-pretreated astrocytes. We found that β-lactolin significantly suppressed ROS production in lipopolysaccharide-stimulated reactive astrocytes (p = 2.76 × 10−6), inhibited MAO-B activity (p = 2.65 × 10−2) and increased intracellular DA levels (p = 1.08 × 10−3), suggesting that β-lactolin could inhibit DA metabolism in astrocytes. These results illustrate the novel protective effects of β-lactolin on reactive astrocytes and suggest their involvement in the memory-improving effects of β-lactolin via the dopaminergic system.